COMMUNITY GARDENING AND THE CAPACITY TO ENRICH SOCIAL BONDING IN URBAN NEIGHBOURHOODS - Shahida Mohd Sharif; Norsidah Ujang (Universitas Trisakti, 2021)
Aim: The aim of this concept paper is to identify a conceptual framework to investigate the level of social bonding/social attachment amongst participants of community gardening activity. It is estimated that more than 50% of the population would be living in urban areas by 2050. One of the drivers is the urban migration, where people are relocating themselves to new neighbourhoods, cities or countries often with the hope of better economic opportunities and social infrastructure, therefore changing the landscape of the new society and the place they reside. It is worrying as these people might not receive enough social support due to their limited social network. It could further escalate to social well-being problems such as individualism and social isolation and could later manifest mentally or psychologically as loneliness. Methodology and Results: This paper argues that the selection of the type of urban green spaces to be integrated into urban neighbourhoods is critical in addressing the well-being problems. Community gardens, as part of urban green spaces, offer meaningful social interaction opportunities, often being missed in the context of modern societies and urban lifestyle. Therefore, there is a need to review the effects of community gardening activities as an intervention strategy to strengthen the degree of social bonding to identify its capacity in integrating isolated people back into community life. Conclusion, significance and impact study: As a conclusion, urban designers and policymakers are suggested to adopt community gardens as a safe open space in cities to encourage more people-people-places interaction.